Investigation of the possible applications for microtextured rolling bearings - Kelley, Josephine; Poll, Gerhard; Pape, Florian (Frontiers in Manufacturing Technology, 2022)
The application of microdimple-textured surfaces for rolling bearings is not very common but can be beneficial for various usage scenarios. In contrast to the applications for plain bearings or cylinder running surfaces, however, surface patterns for rolling bearings only offer advantages under certain conditions. For example, for use with start-stop cycles, in mixed lubrication conditions, or under sliding conditions in a bearing as well as on a roller—bearing flange contact, friction can be reduced with the targeted use of microtextures. The geometry of the microtextures must be chosen so that individual dimples fit in the contact area between the ball or roll and the bearing surface in order to act as a reservoir for the lubricant. First applications for microtextured angular contact ball bearings under oscillating movement conditions proved friction reducing effects under reciprocating motion. In this case the microtextures served as lubricant reservoirs. The idea is transferred to the sliding contact for tapered roller bearings; it is investigated whether the measured reductions in friction are due to the microtextures serving as lubricant reservoirs or whether there is even a positive hydrodynamic effect caused by the microtextures. By means of a calculation approach as well as some exemplary test rig measurements, the behavior for microtextured tapered roller bearings is investigated.